Foot-stretcher angle and rowing performance - Soper, C. (2004)
The rower and coach are challenged with identifying the appropriate skiff setup, technique, and the movement pattern that best fits the rower`s anthropometry and performance level. Limited research has investigated different skiff setups and the impact they have on a rower`s performance. The series of studies in this doctoral thesis aimed to: (1) provide an overview of knowledge regarding the ideal rowing technique from a biomechanical perspective; (2) provide indicators of on-water and ergometer performance reliability; and (3) evaluate experimentally the effects of altering the footstretcher angle on rowing performance and technique.